Conferences in Today Knowledge Society - Santos Martínez, Clara Janneth (Estudios sobre el Mensaje Periodístico, 2013)
Today, Universities are called to create a true scientific culture and raise awareness about the need for scientific and technological literacy, in accordance with the guidelines of the European Space of Higher Education, and favoring a rapprochement of education agents to Knowledge Society. Scientific Communication expressed mainly through publications, conferences, workshops, seminars, and so, is undergoing the changes that the Web 2.0 is experiencing, and is thus creating new roles and functions. Congresses, as media events and a way of socialization of research findingsare involved in this process of transformation by putting into practice a series of innovative experiences, including social networking, which institute a path that leads to new trends such as Cloud Computing.